2016
DOI: 10.3390/ijerph13090843
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Control of Bacterial Pathogens in Cattle Manure

Abstract: Cattle manure harbors microbial constituents that make it a potential source of pollution in the environment and infections in humans. Knowledge of, and microbial assessment of, manure is crucial in a bid to prevent public health and environmental hazards through the development of better management practices and policies that should govern manure handling. Physical, chemical and biological methods to reduce pathogen population in manure do exist, but are faced with challenges such as cost, odor pollution, gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
128
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(138 citation statements)
references
References 108 publications
(157 reference statements)
4
128
0
6
Order By: Relevance
“…Calculated rate of decline for E. coli and Salmonella between sampling dates was within 12.5-21.6 days for one log reduction reported by Goss et al (2013), for September 2010 sampling when manure was relatively warm. Decline rates were higher during the remainder of the study and overall survival rates during storage exceeded those reviewed by Manyi-Loh et al (2016). Nicholson et al (2005) found E. coli O157, Salmonella and Campylobacter survived up to three months in slurry storage compared to 11 mo storage in this study.…”
Section: Agronomic Aspects: Nutrient Contents and Transformationsmentioning
confidence: 45%
See 1 more Smart Citation
“…Calculated rate of decline for E. coli and Salmonella between sampling dates was within 12.5-21.6 days for one log reduction reported by Goss et al (2013), for September 2010 sampling when manure was relatively warm. Decline rates were higher during the remainder of the study and overall survival rates during storage exceeded those reviewed by Manyi-Loh et al (2016). Nicholson et al (2005) found E. coli O157, Salmonella and Campylobacter survived up to three months in slurry storage compared to 11 mo storage in this study.…”
Section: Agronomic Aspects: Nutrient Contents and Transformationsmentioning
confidence: 45%
“…From soil, pathogens may be transferred into waterways to become a human health hazard (Goss and Richards 2008;Jacobsen and Bech 2012). However, results of pathogen survival in laboratory condition are known to differ from those under field condition (Manyi-Loh et al 2016), thus, knowledge of the type and amounts of pathogens and their survival rates in farm storages is needed to improve estimates of risks from land application of manure.…”
mentioning
confidence: 99%
“…more resistant to the condition and temperature of the digester. Factors affecting the hygiene of the digester depend on the pathogens present in the feed material, their amount, the temperature of the biogas process, retention time, process type and available nutrients [24,25]. The reduction of endoparasites in CBM formation process reached 77.08%, whereas in the previous study the reduction of endoparasites in the biogas formation process reached 93.7% [26].…”
Section: Total Number Of Bacteriamentioning
confidence: 79%
“…These are known as manure-borne pathogens (Pachepsky et al 2006, Manyi-Loh et al 2016. A minimum of three months is needed when the air is more than 0°C to properly kill microbes in untreated, dry manure (Manyi-Loh et al 2016). This is problematic in Mongolia where during much of the year the ambient temperature is below 0°C.…”
Section: Zoonotic Risks: Fuel and Water Sourcesmentioning
confidence: 99%
“…A review of zoonotic pathogens associated with cattle manure found that Salmonella spp., Campylobacter spp., Listeria monocytogenes, Yersinia enterocolitica, Escherichia coli, Cryptosporidium parvum, and Giardia lamblia were all spread in manure. These are known as manure-borne pathogens (Pachepsky et al 2006, Manyi-Loh et al 2016. A minimum of three months is needed when the air is more than 0°C to properly kill microbes in untreated, dry manure (Manyi-Loh et al 2016).…”
Section: Zoonotic Risks: Fuel and Water Sourcesmentioning
confidence: 99%